Inadequacy of consumer protections from unfair contract terms in Musharakah Mutanaqisah home financing in Malaysia - Mat Ali, Syuhaeda; Hassan, Rusni; Othman, Ahmad Azam (IIUM Press, 2017)
Musharakah Mutanaqisah is one of the Islamic home financing products which has gained popular demand from the public in Malaysia. However, the terms and conditions of legal documentation of Musharakah Mutanaqisah Home Financing which were usually prepared by solicitors for Islamic financing institutions (“IFIs”) may have affected the welfare of consumers especially when most of the terms and conditions of legal documentations favoured the IFIs. In these circumstances, the consumers have no choice but to abide by the terms stipulated by the IFIs.This paper examines the adequacy of present legislation in Malaysia namely Islamic Financial Services Act 2013, Financial Services Act 2013, Shariah Standard and Guidelines: Prohibited Business Conduct policy, Consumer Protection Act 1999, Consumer Protection (Amendment) Act 2010 and the Contracts Act 1950 relating to unfair terms of contract in Musharakah Mutanaqisah Home Financing. The methodology adopted in this paper is statutory analysis whereby the relevant legislation are analysed. The analysis reveals that the legislation are not sufficient to regulate unfair terms of contract in Musharakah Mutanaqisah Home Financing in Malaysia. To ensure the protection of the consumers in Musharakah Mutanaqisah Home Financing, this paper recommends the present legislation, particularly Consumer Protection Act 1999 and Contracts Act 1950 be reformed. Musharakah Mutanaqisah Home Financing, reform, legislation, standard form of contract.